2023
DOI: 10.3390/ijms241813997
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum LPJZ-658 Improves Non-Alcoholic Steatohepatitis by Modulating Bile Acid Metabolism and Gut Microbiota in Mice

Liming Liu,
Liquan Deng,
Wei Wei
et al.

Abstract: Non-alcoholic steatohepatitis (NASH) is one of the most prevalent diseases worldwide; it is characterized by hepatic lipid accumulation, inflammation, and progressive fibrosis. Here, a Western diet combined with low-dose weekly carbon tetrachloride was fed to C57BL/6J mice for 12 weeks to build a NASH model to investigate the attenuating effects and possible mechanisms of Lactiplantibacillus plantarum LPJZ-658. Hepatic pathology, lipid profiles, and gene expression were assessed. The metabolomic profiling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Our practice has confirmed that LPJZ-658 improves lipid metabolism in late-laying laying hens and broiler chickens [39]. It is important to note that we found that LPJZ-658 ameliorated hepatic steatosis, inflammation, and fibrosis in NASH model mice by mediating bile acid metabolism and the gut microbiota [29], which suggests that LPJZ-658 has the potential to improve MASLD. In this study, copper deficiency combined with a high-sugar-diet-induced MASLD mouse model was used to explore the therapeutic mechanism of LPJZ-658 in MASLD-combined lipidomics, metabolomics, and gut microbiota strategies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our practice has confirmed that LPJZ-658 improves lipid metabolism in late-laying laying hens and broiler chickens [39]. It is important to note that we found that LPJZ-658 ameliorated hepatic steatosis, inflammation, and fibrosis in NASH model mice by mediating bile acid metabolism and the gut microbiota [29], which suggests that LPJZ-658 has the potential to improve MASLD. In this study, copper deficiency combined with a high-sugar-diet-induced MASLD mouse model was used to explore the therapeutic mechanism of LPJZ-658 in MASLD-combined lipidomics, metabolomics, and gut microbiota strategies.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, metabolomics may provide more insights and clues for the present study on the development and progression of copper deficiency combined with sugar-induced MASLD and the mechanism of action of LPJZ-658. In our previous studies, LPJZ-658 has been found to affect multiple metabolic pathways, especially bile acid biosynthesis [29].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A robust correlation exists between the gut microbiota and serum metabolites. Using 16S rRNA sequencing and serum metabolomics, Oscillibacter demonstrated a positive correlation with chenodeoxycholic acid, glycocholic acid, and deoxycholic acid [18]. The glucose and lipid metabolic pathways in the host can be modulated using SCFAs originating from microbial sources, and SCFAs have the capacity to exert an influence on immune function and inflammation [19].…”
Section: Introductionmentioning
confidence: 99%